The Investigation of Teacher’s Questioning Strategies in Speaking Class - Aulia Rusdy; Asnawi Muslem; Muhammad Aulia (Research in English and Education Journal, 2023)
This research aimed to discover the questioning strategies that English teachers used in speaking class and why English teachers used the questioning strategies in speaking class at SMP Negeri 5 Lhokseumawe. This research applied a descriptive qualitative method. The data were collected from the observation by video-recording and interview. This study focused on the theory proposed by Wragg Brown (1993, as cited in Irawati et al., 2021). The data were taken from two English teachers at SMP Negeri 5 Lhokseumawe to determine the questioning strategies. In analyzing the data, the researcher used descriptive analysis. This research showed that the teacher used questioning strategies, such as structuring, directing, distributing, prompting and probing, listening to replies and responding, and pausing and pacing. Furthermore, there were two types of questioning strategies the teachers could not use in speaking class: pitching and putting clearly, and sequencing. Moreover, the underlying  reason why the English teacher used the questioning strategies to increase students' activity and to measure students' knowledge about the material.